KEWAJIBAN PENYIDIK DALAM MEMANGGIL DAN MEMERIKSA SAKSI A DE CHARGE - Mochammad Zulfi Yasin Ramadhan (Jurnal Penegakan Hukum Indonesia, 2021)
Investigators also have an obligation to serve the interests of the the suspect, when they ask to be presented with a witness who according to their version can help to break the elements or discharge them from the suspicion, this kind of witness is known as A De Charge (Exoneration Witness). The problem arises how to assess and screen and summon an a de charge witnesses. Investigators must have a clear and complete ground for implementing this provision. Based on that issue, the problem formulations in this study are as follows: (1) What are the criteria for a de charge witnesses who can be examined by investigators? (2) What are the sanctions for investigators when refusing to call and examine a de charge witnesses? The research method used in this paper is a normative research method with a statutory and conceptual approach. The results show that the neglect of the a de charge witness examination has made the norms governing the examination of a de charge witnesses becomes less crucial, which should receive serious attention in investigations for the realization of a criminal justice that upholds the principle of fair trial.